The Conceptualization of God's Dwelling Place in 1 Kings 8: A Cognitive Approach - Kamp, Albert H. (Journal for the study of the Old Testament, 2016)
The diversity of terms for God's dwelling place in 1 Kings 8 is generally ascribed to a number of text traditions in which different theological views of the temple and God's dwelling place dominate. Rather than taking a fragmented view, this study starts from the textual integrity of 1 Kings 8. It investigates how the conceptualization of God's dwelling place is given shape within the text. With the help of insights from cognitive linguistics, in particular ‘Text World Theory’, the communicative structure of 1 Kings 8 is first revealed. Subsequently, attention is paid to the linguistic presentation of words and word constructions and their contribution to the conceptualization of lexical content. The way in which God ‘dwells’, where he ‘lives’ and in what form he ‘appears’ form a coherent picture in 1 Kings 8 which emphasizes the ontological distinction between God and human beings.